Late early Miocene caviomorph rodents from Laguna del Laja (~37° S), Cura-Mallín Formation, south-central Chile. (October 2020) - Solórzano, Andrés; Encinas, Alfonso; Kramarz, Alejandro; Carrasco, Gabriel; Montoya-Sanhueza, Germán; Bobe, René
Abstract: Despite recent efforts, the paleodiversity of the Neogene mammals in Chile remains poorly known, with several putative new species awaiting description. For example, previous studies suggest that the early to late Miocene mammalian assemblages from the Laguna del Laja fossiliferous locality (Cura-Mallín and Trapa-Trapa formations), which crop out in the Andean Cordillera of Chile (~37°), comprise dozens of undescribed taxa. A better understanding of the taxonomic affinities of the Laguna del Laja faunas is needed, as it represents one of the few faunas known from the early to late? Miocene of the south-central Andean main range. Several specimens of caviomorphs recently recovered in late early Miocene beds of the Cura-Mallín Formation at Laguna del Laja are here described in detail, and a brief discussion of their chronological, biogeographical, and paleoenvironmental significance is also provided. Based on fragments of mandible, maxilla and isolated teeth five taxa were recognized, Phanomys mixtus Ameghino, Prolagostomus sp., Neoreomys sp., Maruchito nov. sp.?, and Luantus sompallwei nov. sp. The radiometric ages of the fossil-bearing horizons, constrained between 17.7 and 16.4 Ma, as well as the common species ( P. mixtus ) and genera ( Prolagostomus and Neoreomys ) indicate that the fauna here reported belongs to the Santacrucian SALMA. Finally, our finding preliminary suggests the predominance of rather open habitats in the Cura-Mallín Formation during this time, but also a widely distributed late Early Miocene caviomorph fauna along the southern Andes, in both intra-arc and foreland basins. Highlights: A late early Miocene rodent assemblage of the Cura-Mallín Formation at Laguna del Laja (Chile) is analyzed here. A new species of caviomorph rodent is described: Luantus sompallwei. Phanomys mixtus Ameghino is for the first time reported in Chile. The rodent assemblage here studied might be related to the Santacrucian SALMA.